Detection of Calcareous Corpuscles in Spargana of Spirometra Species by Histological Studies - Kavana, Nicholas J. (Innovations in Biological Science Vol. 10, 2024)
Tissues of sparganum of Spirometra (a larval stage) contain mineral concretions termed calcareous corpuscles. These corpuscles serve as a focal deposition of calcium protecting the larvae against calcification. Calcareous corpuscles are believed to form either intracellular or extracellular and the cell type involved, the place of formation and the mechanism of mineral deposition seem to be also diverse. In the present study, histological studies of spargana were made at the light microscope level. It was intended to ascertain if calcareous corpuscles are present in the body of sparganum of Spirometra species. Spargana recovered from naturally infected frogs (R. cancrivora) had thick heads and thin bodies. The result of histological sections of the spargana stained with Haematoxylin-eosin showed calcareous corpuscles which were ovoid in shape and irregularly distributed in the parenchyma of the body of spargana. A total of 13 spargana were measured and the range of length was 11–50 mm and width 0.5–1.5 mm. The mean measurements were 27.6 x 0.9 mm. In conclusion, the spargana of Spirometra species have calcareous corpuscles in the body parenchyma.